Tocilizumab treatment for COVID-19 patients: a systematic review and meta-analysis - Qiu Wei; Hua Lin; Rong-Guo Wei; Nian Chen; Fan He; Dong-Hua Zou; Jin-Ru Wei (BMC, 2021)
Abstract Background Coronavirus disease 2019 (COVID-19) has killed over 2.5 million people worldwide, but effective care and therapy have yet to be discovered. We conducted this analysis to better understand tocilizumab treatment for COVID-19 patients. Main text We searched major databases for manuscripts reporting the effects of tocilizumab on COVID-19 patients. A total of 25 publications were analyzed with Revman 5.3 and R for the meta-analysis. Significant better clinical outcomes were found in the tocilizumab treatment group when compared to the standard care group [odds ratio (OR) = 0.70, 95% confidential interval (C): 0.54-0.90, P = 0.007]. Tocilizumab treatment showed a stronger correlation with good prognosis among COVID-19 patients that needed mechanical ventilation (OR = 0.59, 95% CI, 0.37-0.93, P = 0.02). Among stratified analyses, reduction of overall mortality correlates with tocilizumab treatment in patients less than 65 years old (OR = 0.68, 95% CI: 0.60-0.77, P < 0.00001), and with intensive care unit patients (OR = 0.62, 95% CI: 0.55-0.70, P < 0.00001). Pooled estimates of hazard ratio showed that tocilizumab treatment predicts better overall survival in COVID-19 patients (HR = 0.45, 95% CI: 0.24-0.84, P = 0.01), especially in severe cases (HR = 0.58, 95% CI 0.49-0.68, P < 0.00001). Conclusions Our study shows that tocilizumab treatment is associated with a lower risk of mortality and mechanical ventilation requirement among COVID-19 patients. Tocilizumab may have substantial effectiveness in reducing mortality among COVID-19 patients, especially among critical cases. This systematic review provides an up-to-date evidence of potential therapeutic role of tocilizumab in COVID-19 management. Graphical abstract